Penanaman Nilai-Nilai Karakter Religius Santri Di Pondok Pesantren Nadlatul Quran - Rahmad Hulbat (PT. Pustaka Andil Lestari, 2024)
Instilling religious character values is something that has been relatively old in the world of Islamic education. This is deemed necessary to be realized, especially values that are directly related to the moral formation of the nation. This research aims to reveal the religious character values of the Islamic boarding school students that are instilled and the methods used to instill the religious character values of the Islamic boarding school students at the Nadlatul Quran Islamic Boarding School. This research uses a qualitative approach. Data collection was carried out using interview, observation and documentation techniques. Data analysis techniques include data collection, data education, data presentation and drawing conclusions, checking the validity of the data is carried out by expanding the role of researchers: triangulation techniques using various sources, theories and methods, and persistent observation of research information, namely all religious teachers and students. The results of the research show that: (1) instilling religious character values for students at the Nadlatul Quran Islamic Boarding School, including several values such as: (a) religious, (b) honest, (c) tolerance, (d) discipline, (e) work tough, (f) independent, (g), love peace, (h) care for the environment, (i) religious character values of responsibility, (j) nationalism/national spirit, (k) love of the homeland, j) communicative, friendly, happy (l) appreciates achievements, (m) social care, (n) tough, (o) polite, (p) clean, (q) frugal, (r) patient, efficient. (2) Methods for instilling religious character values in students at the Nadlatul Quran Islamic Boarding School, including: (a) example, (b) habituation, (c) conditioning advice, (d) prohibitions and commands, (e) telling stories, (f ) memorize. Keywords: Cultivation, Religious Character Values, and Santri.